Answer:
(c, d) = (25, 35)
Step-by-step explanation:
Multiply the first equation by 2.5 and subtract the second one:
2.5(c +d) -(2.5c +1.75d) = 2.5(60) -(123.75)
0.75d = 26.25 . . . . . . . . . simplify
26.25/0.75 = d = 35 . . . . divide by the coefficient of d
60 -d = c = 25 . . . . . . . . . use the first equation to find c
(c, d) = (25, 35)
Answer:
1 answer
Step-by-step explanation:
when the terms are collected
Answer:
(2x + 3)(x - 2)
Step-by-step explanation:
use FOIL
First, Outside, Inside, Last
2x x x = 2x²
2x x -2 = -4x
3 x x = 3x
3 x -2 = -6
2x² - 4x + 3x - 6
Is it 5^6 - 5^11 = 5x × (1-5y)?
5^6 - 5^11 = 5^(6-11) = 5^(-5) = 1/(5^5)
So 1/3125 = 5x - 5(5y)
1/3125 = 5(x-5y)
1/3125/5 = x-5y
0.000064 = x - 5y
Answer:64
Step-by-step explanation: